Extended dual antithrombotic therapy in patients with chronic coronary syndrome — which agent should be added to aspirin? - Jacek Kubica; Piotr Adamski; Katarzyna Buszko; Piotr Buszman; Nader Elmasri; Tomasz Fabiszak; Jakub Foryś; Robert Gajda; Mariusz Gąsior; Robert Gil; Paweł Grzelakowski; Tomasz Hajdukiewicz; et al. (Cardiology Journal)
According to the 2024ESC Guidelines for the management of chronic coronary syndromes dual antithrombotic treatment comprising aspirin and a second antithrombotic drug for extended long-term prevention should be considered in patients at increased ischemic risk without high bleeding risk. However, no clear indications regarding the choice of a second antithrombotic agent are provided. It was therefore decided to discuss the available evidence regarding this issue. The guidelines provided the number needed to treat (NNT) and the number needed to harm (NNH) for each proposed medication. However, the presented data are misleading and may result in unjustified therapeutic decisions. Due to the great impact of this document on clinical practice all data provided in this document should be carefully verified and commented regarding limitations.